RANCANG BANGUN SISTEM DETEKSI TITIK KEBAKARAN DENGAN METODE FUZZY LOGIC BERBASIS IOT PADA MTS AL-DZIKRI - Rita Septiani; Iwan Giri Waluyo (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
MTSS AL-DZIKRI is one of the private schools in Cimanggu sub-district, Pandeglang district, Banten province and the only school in Kp. Pasirnangka. MTSS AL-DZIKRI was established on August 10, 2018, this school is still relatively new but its development is very fast so that there are many enthusiasts from various circles of society, MTSS AL-DZIKRI also provides dormitory facilities. Fire events can occur anywhere, whether in schools, public places or housing. In the process of fire itself always arises due to the process of energy changes and changes in materials. This tool works by means of a flame sensor receiving heat input and the water pump will turn on to extinguish the fire after the fire has been extinguished, the water pump will turn off automatically, the process is controlled by the NodeMCU esp8266, and this tool can also provide notifications if something happens. fire through the application on the smartphone. The method used is fuzzy logic as a method for controlling the water pump control system, the fuzzy logic method has several stages, namely fuzzyfication, inference, and defuzzification. The development method used in this research is the prototype method. And the system testing method used is the black box method. Based on the implementation and testing of the system, it can be said that this IoT-based automatic fire point detection tool can help schools.